ANALISA OPTIMASI KEUNTUNGAN PENJUALAN KOPI CARAMEL ESPRESSO DAN AMERICANO DI KEDAI KUDUKUMAHA MENGGUNAKAN METODE GRAFIK LINEAR PROGRAMMING - Amrullah, Muhammad (Journal of Industrial and Engineering System, 2024)
Coffee shops continue to develop as a business with increasingly fierce competition. To maintain and increase competitiveness, shop owners need to optimize their production and sales strategies. This research aims to optimize profits from the production of two popular coffee variants, namely Caramel Espresso and Americano, at Kedai Kudukumaha using the Linear Graphic Programming method. Through collecting data related to price, market demand, production costs and production capacity, we build mathematical models that help in making smarter decisions regarding resource allocation and pricing. The Graphic Linear Programming method is used to find the optimal point in the solution space that maximizes profits. The research results show that implementing the strategy resulting from this analysis can significantly increase the production profits of the two coffee variants. We hope that this research can add valuable insight for coffee shop owners and other stakeholders in the development of the coffee industry to improve operational efficiency and make more informed decisions to increase competitiveness and profitability.